PENDAMPINGAN PENYUSUNAN LAKIP BERBASIS AKUNTANSI PERTANGGUNGJAWABAN DI KALIMANTAN TENGAH - Nadia Dara Amirue; Jhon Lis Berger; M. Ichsan Diarsyad; Heru Pribowo (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
The Impactful Independent Internship Program (MBKM) at the Bureau of Government and Regional Autonomy, Administrative Division of the Regional Secretariat of Central Kalimantan Province carried out this community service project for four months, from January 22 to May 22. This activity aimed to improve the quality of performance report preparation through more systematic and measurable data management. A qualitative descriptive method was employed through participant observation, unstructured interviews, and examination of institutional performance records. The students assisted in managing government administration, collecting performance data, and preparing physical and financial realization reports. The results of the activity indicated that the implementation of responsibility accounting through the identification of responsibility centers, measurement of performance indicators, and verification of supporting documents was able to improve the accuracy and quality of LAKIP preparation. This activity also contributed to enhancing students’ competencies in public sector accounting and improving the administrative effectiveness of government institutions.